ANALISIS PENATAUSAHAAN BARANG MILIK DAERAH DI KABUPATEN SIGI - Diana Arianti (Katalogis, 2018)
Administration of regional property is component in asset management that has important role in local financial statements. According to the law of the Ministry of Demostic Affairs number 17 year 2007 about technical guidance of regional property management, property administration is divided into three activities that are accounting, inventory, and reporting. The Department of Regional Revenue and Asset Administration in Sigi Regency has not effectively managed its property for three reasons : 1) lack of competence of human resources due to lack of training and job rotation; 2) lack of infrastructure of 46 governmental working units in Sigi, only 7 units have storage warehouses because their effices are still renting. In addition, lack of maintanence; 3) System, functions and duties of property administration averlap, the role of the administrator is overlooked because the distribution of property is directly to the working units.